Trends in Islamic entrepreneurship research: A perspective on developing the independence of Islamic boarding school students in Indonesia - Juliyani, Erly (Universitas Islam Indonesia, 2025)
IntroductionIslamic entrepreneurship has gained increasing attention as an approach that integrates sharia-based ethical values with economic activity, particularly in Muslim-majority contexts such as Indonesia. Islamic boarding schools (pesantren) are socio-religious institutions that have expanded their roles beyond religious education into economic empowerment and entrepreneurial development. However, research on pesantren-based Islamic entrepreneurship remains fragmented across disciplines and often limited to localized case discussions, making it difficult to form a comprehensive understanding of research trends, program models, and determinants of institutional economic independence.ObjectivesThis study systematically reviews the development of Islamic entrepreneurship research related to strengthening the economic independence of pesantren in Indonesia. It aims to identify dominant research themes, assess methodological patterns, examine internal and external factors influencing entrepreneurship implementation, and highlight underexplored areas that can inform future research and policy development.MethodA systematic literature review was conducted using scholarly publications drawn from accredited national and international databases. Using inclusion criteria focused on thematic relevance, academic quality, and the Indonesian pesantren context, 42 eligible studies published between 2014 and 2024 were selected. The review applied qualitative thematic content analysis to classify research topics, program types, institutional roles, implementation challenges, theoretical frameworks, and reported economic outcomes.ResultsThe findings indicate a notable rise in pesantren-centered Islamic entrepreneurship research since 2019, with implementation-focused studies dominating the literature. Common program models include technical skills training, student business units, and collaboration with local micro, small, and medium enterprises. Reported outcomes suggest that entrepreneurship initiatives contribute to pesantren economic independence by increasing internal income and reducing dependence on external funding. The review also identifies persistent constraints, including limited capital access, insufficient managerial capacity, and weak external stakeholder collaboration. Evidence further suggests that human resource quality and effective entrepreneurial management strengthen the relationship between Islamic entrepreneurship practices and institutional independence.ImplicationsThis review underscores pesantren as strategic institutions for sharia-based economic empowerment and highlights the importance of capacity building, multi-stakeholder partnerships, and sustainable entrepreneurial ecosystem development aligned with Islamic ethical commitments.Originality/NoveltyBy providing a structured synthesis of dispersed scholarship, this study offers an integrated map of research trends and critical enabling factors, strengthening the conceptual foundation for pesantren-based Islamic entrepreneurship and supporting more contextually relevant strategies for sustainable economic independence.